2006
DOI: 10.1614/wt-04-070r1.1
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Various Market Classes of Dry Beans (Phaseolus vulgarisL.) to Linuron

Abstract: Tolerance of eight market classes of dry beans (black, brown, cranberry, kidney, otebo, pinto, white, and yellow eye beans) to the PRE application of linuron at the rate of 2.25 and 4.50 kg ai/ha was studied at two locations in Ontario, Canada, in 2003 and 2004. The eight market classes differed in their response to linuron. Linuron PRE caused as much as 43, 20, 7, 17, 54, 36, 56, and 12% visual injury in black, brown, cranberry, kidney, otebo, pinto, white, and yellow eye beans, respectively. Linuron PRE at 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
3
7
0
Order By: Relevance
“…This is consistent with other studies that have shown similar responses with soil applications of S-metolachlor, imazethapyr, flumioxazin, and linuron Soltani et al 2003Soltani et al , 2004Soltani et al , 2005Soltani et al , 2006.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with other studies that have shown similar responses with soil applications of S-metolachlor, imazethapyr, flumioxazin, and linuron Soltani et al 2003Soltani et al , 2004Soltani et al , 2005Soltani et al , 2006.…”
Section: Resultssupporting
confidence: 92%
“…White (navy) beans were found to be more sensitive to EPTC than pinto and light red kidney beans and black and white beans were more sensitive to alachlor than Great Northern, pinto, cranberry, and pink beans (Urwin et al 1996). Large-seeded market classes of dry beans were more tolerant to linuron than small-seeded market classes (Soltani et al 2006). White beans are more sensitive to alachlor than red kidney beans (Doersch et al 1974).…”
mentioning
confidence: 99%
“…Cloransulammethyl (35 g ai.ha -1 ), linuron (2250 g ai.ha ) provided up to 8%, 44%, 21%, 18%, and 2% control 4 WAE ( Table 2) and up to 6%, 24%, 14%, 8%, and 0% control 8 WAE, respectively ( Table 3). This is consistent with research in Phaseolus vulgaris, where Soltani et al [12] found linuron injured black bean (27%) and white bean (31%) at 4 WAE. In addition, a study evaluating flumetsulam use in southern pea (Vigna unguiculata L.) reported that there was crop injury of 13% at 3 WAA, demonstrating southern pea's relative tolerance to flumetsulam [13].…”
Section: Pre-emergence Herbicidessupporting
confidence: 92%
“…Soltani and Sikkema (2005) reported that cloransulam‐methyl applied PPI to white bean resulted in ≤10% crop injury, which is considered to be commercially acceptable, but it reduced the plant height, biomass, and yield in comparison to an untreated control. Soltani et al. (2008b) found that halosulfuron‐methyl applied PPI at 35 and 70 g ai ha −1 caused minimal crop injury and did not reduce the plant height or yield of several market classes of dry bean.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, several studies have reported that halosulfuron‐methyl has an adequate margin of crop safety for several market classes of bean (Silvey et al. 2006; Soltani et al. 2008b).…”
mentioning
confidence: 99%